Challenges to evidence-based health promotion: a case study of a Food Security Coalition in Ontario, Canada. (30th March 2017) - Meyer, Samantha B; Edge, Sara S; Beatty, Jocelyn; Leatherdale, Scott; Perlman, Chris; Dean, Jennifer; Ward, Paul R; Kirkpatrick, Sharon I
Summary: Developing the evidence base for health promotion can be challenging because interventions often have to target competing determinants of health, including social, structural, environmental and political determinants; all of which are difficult to measure and thus evaluate. Drawing on a case study of food insecurity, which refers to inadequate access to food due to financial constraints, we illustrate the challenges faced by community-based organizations in collecting data to form an evidence base for the development and evaluation of collective programmes aimed at addressing food insecurity. Interviews were conducted with members of a multi-stakeholder coalition ( n = 22 interviewees; n = 10 organizations) who collectively work to address food insecurity in their community through a range of community-based programmes and services. Member organizations also provided a list of measures currently used to inform programme and service development and evaluation. Data were collected in a city in Southern Ontario, Canada between May and September 2015. Participants identified four barriers to collecting data: Organizational needs and philosophies; concerns surrounding clientele wellbeing and dignity; issues of feasibility; and restrictive requirements imposed by funding bodies. Participants also discussed their previous successes in collecting meaningful data for identifying impact. Our results point to the challenge of generating data suitable for developing and evaluating programmes aimed at broader determinants of health, while maintaining the primary goal of meeting clients' needs. Documenting change at intermediate- and macro-levels would provide evidence for the collective effectiveness of current programmes and services offered. However, appropriate resources need to be invested to allow for scientific evaluation.